Mimosa brevicalyx (Leguminosae-Caesalpinioideae): a new species based on molecular, anatomical, and morphological data - Mendes, Thainara Policarpo [UNESP]; Simon, Marcelo Fragomeni; Alonso, Alexandre Antonio; Silva, Marcos Jose da [UNESP] (Springer, 2021)
Phylogenetic, taxonomic, and biogeographic studies of Mimosa sect. Mimosa ser. Mimosa subser. Polycephalae revealed a new species, Mimosa brevicalyx T.P.Mendes & M.J.Silva (sp. nova), endemic to the savannas of central Goias State, Brazil. The species is described here, illustrated, compared with related taxa (Mimosa hypoglauca var. hypoglauca, M. hypoglauca var. dawsonii, M. papposa var. papposa, and M. papposa var. segrex), its geographic distribution is mapped, its conservation status, flowering and fruiting times and systematic position is discussed, and images are provided. Additionally, the new species and its related congeners have their phylogenetic positions elucidated and discussed based on molecular phylogenies derived from the union of ITS (nrDNA) and trnD-T (cpDNA) markers and are compared using leaf-anatomical data, including the micromorphology of its trichomes. Trichomes are of extreme importance for determining the taxa considered here, as they show stable and discontinuous differences related to the environments occupied by the species and are therefore all of likely ecological relevance.
Keywords: Brazilian savannas; Mimosa ser; mimosa subser; polycephalae; Phylogeny; Taxonomy